2013
DOI: 10.1177/1468087413482320
|View full text |Cite
|
Sign up to set email alerts
|

Fuel property and fuel temperature effects on internal nozzle flow, atomization and cyclic spray fluctuations of a direct injection spark ignition–injector

Abstract: The effect of fuel properties and fuel temperature on the behaviour of the internal nozzle flow, atomization and cyclic spray fluctuations is examined for a three-hole direct injection spark ignition injector by combining numerical simulation of the nozzle flow with macroscopic and microscopic spray visualization techniques. A dominant influence of the liquid fuel viscosity on the highly unsteady, cavitating nozzle flow and spray formation was observed. A reduced viscosity (or larger Reynolds number) increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…There, the spray is sometimes more bent to the "left" or to the "right" while sometimes larger recirculation zones appear at one side, which push the spray in the opposite direction. These vortices and the general spray fluctuations are generated by spray-induced turbulence in the chamber and also by the highly unsteady, cavitating nozzle flow (which leads to variations of the cone angle and bent angle already in the near-nozzle region) [43]. Furthermore, the individual jet may be additionally bended due to jet-to-jet interactions.…”
Section: (2)mentioning
confidence: 99%
“…There, the spray is sometimes more bent to the "left" or to the "right" while sometimes larger recirculation zones appear at one side, which push the spray in the opposite direction. These vortices and the general spray fluctuations are generated by spray-induced turbulence in the chamber and also by the highly unsteady, cavitating nozzle flow (which leads to variations of the cone angle and bent angle already in the near-nozzle region) [43]. Furthermore, the individual jet may be additionally bended due to jet-to-jet interactions.…”
Section: (2)mentioning
confidence: 99%
“…These spatial and temporal variations are also dependent on fuel properties. For example, Zigan et al 7 showed that the liquid fuel viscosity plays a major role in the internal nozzle flow and spray propagation and determines cyclic variations in the shape of DISI sprays. These experiments were conducted for alkane fuels (n-hexane, n-decane) under normal ambient conditions (0.1 MPa, 25 C).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic variations have their origin in turbulent fluctuations. [3][4][5][6] It is also well known that gasto-wall heat flux depends highly on turbulence. All these effects are of major interest for the simulation of an engine cycle.…”
Section: Introductionmentioning
confidence: 99%